Dziewiętnastowieczne wydania polskich przekładów pism Świętej Teresy z Ávili - Kacprzak, Marta M. (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2021)
From the 1840’s to the end of the 19th century more than twenty editions of Polish translations of texts by Saint Teresa of Ávila, as well as the ones attributed to her, were released. It was attempted to popularise her works, information about her life and thought, as well as the cult of her, knowledge about Christian mysticism and the revival of religious life. Two important bibliographies presenting the reception of Teresa in Poland: one by Stefania Ciesielska-Borkowska (1939) and the other one by Benignus Wanat (1972) require complementing and corrections, which should find reflection in contemporary editions and catalogues. The paper presents all the editions of works by Teresa (fragments, all works, collections of works, as well as paraphrases), released in Polish in the 19th-century books and periodicals. It corrects the mistakes in bibliographical descriptions, which result from mistakes in the publications themselves, as well as errors in attribution. It refers to the authorship of anonymous translations and their undetermined bases, it characterises briefly the environments in which Saint Teresa’s works were translated and published. It presents the religious, literary, social and scientific purposes accompanying the texts by Teresa, as well as translation, editorial and ideological assumptions. It shows the editions of Saint Teresa’s texts in translations or paraphrases by: Sebastian Nucerin, Ignacy Hołowiński, Nina Łuszczewska, Eleonora Ziemięcka, Michał Bohusz Szyszko, Eleonora z Paprockich Szemiothowa, Zygmunt Krasiński, Lucjan Siemieński, Ignacy Domeyko, Karmela Wiktima od Jezusa (Amalia Zenopolska), Tadeusz Miciński, Henryk Piotr Kossowski, as well as anonymous translators.